2010
DOI: 10.1111/j.1365-2249.2010.04226.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant anti-tumour activity of adoptively transferred T cells elicited by intratumoral dendritic cell vaccine injection through enhancing the ratio of CD8+ T cell/regulatory T cells in tumour

Abstract: SummaryWe have shown that immunization with dendritic cells (DCs) pulsed with hepatitis B virus core antigen virus-like particles (HBc-VLP) packaging with cytosine-guanine dinucleotide (CpG) (HBc-VLP/CpG) alone were able to delay melanoma growth but not able to eradicate the established tumour in mice. We tested whether, by modulating the vaccination approaches and injection times, the anti-tumour activity could be enhanced. We used a B16-HBc melanoma murine model not only to compare the efficacy of DC vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In cancer, they are critically important for activating CD8 + T cells into potent cytotoxic T cells capable of lysing tumor cells (22,23). DCs are indeed capable of inducing T eff , depending on the stimulus by which these DCs have been activated.…”
mentioning
confidence: 99%
“…In cancer, they are critically important for activating CD8 + T cells into potent cytotoxic T cells capable of lysing tumor cells (22,23). DCs are indeed capable of inducing T eff , depending on the stimulus by which these DCs have been activated.…”
mentioning
confidence: 99%
“…Lutz-Nicoladoni et al [27] as well as Koike et al [26] showed delayed tumor outgrowth or better survival and tumor regression as a result of this combination treatment in >40 % of animals inoculated with aggressive tumors. Song et al [29] as well as Tamai et al [30] had similar findings and showed that combination treatment led to T cell infiltration into the primary tumor, as well as into metastases and induced immunological memory that protected the mice from re-challenge.…”
Section: Discussionmentioning
confidence: 64%
“…Studies from several mouse models have suggested that the combination of DC vaccination with ACT is superior to single agent treatments [26][27][28][29][30]. Lutz-Nicoladoni et al [27] as well as Koike et al [26] showed delayed tumor outgrowth or better survival and tumor regression as a result of this combination treatment in >40 % of animals inoculated with aggressive tumors.…”
Section: Discussionmentioning
confidence: 95%
“…administered Type-1 anti-tumor CD8 + T cells in a CXCL10/IP-10 chemokine-dependent manner (60). Also in this light, several recent reports (61–63) are intriguing since i.t. delivery of DC loaded with tumor antigens (versus unloaded DC) was observed to maximally enhance the accumulation and anti-tumor efficacy of adoptively-transferred or vaccine-induced tumor antigen-specific CD8 + T cells.…”
Section: Discussionmentioning
confidence: 92%